ACTUALIZATION OF PANCASILA VALUES IN THE MANGURE LAWIK TRADITION AS AN EFFORT TO PRESERVE LOCAL WISDOM IN SIBOLGA CITY - Junaidi, Junaidi; Sundawa, Dadang (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
The younger generation is increasingly drawn into modern culture, which often contradicts the noble values of the nation. This has resulted in a diminishing appreciation for traditions, customs, and social norms passed down by ancestors. Therefore, the aim of this research is to uncover the values of Pancasila in the Mangure Lawik tradition as an effort to preserve local wisdom in the city of Sibolga. The research method used is qualitative with a descriptive approach. Data collection employs primary data through interviews, observations, and documentation, as well as secondary data from books, journals, and relevant sources. Data analysis is performed using Miles and Huberman's analysis method, which includes data reduction, data display, and data verification. The results show that the Mangure Lawik tradition in Sibolga reflects the values of Pancasila, particularly in terms of togetherness and reverence for God. This ritual is performed as a form of gratitude to God for the harvest from the sea and a prayer for the safety of the fishermen. The tradition also demonstrates the values of solidarity and mutual cooperation. Furthermore, Mangure Lawik embodies the value of Indonesian unity, with active participation from all layers of society in this festival. This tradition also reflects the value of social justice, where the entire coastal community is involved in cultural activities and environmental preservation, strengthening unity and national identity. Today, the tradition continues to guide the community’s Pancasila-based lifestyle, shaping policies and youth participation in preserving both culture and nature.